PERAN MAHASISWA KKN DALAM PEMBERDAYAAN MASYARAKAT DESA CIPADA DI BIDANG PENDIDIKAN - Arobiansyah, Novaldi; Dwi Yulianto, Marsel; Fauzia, Dara; Rahmadini, Salsa; Nirmalawati, Syifa; Solihin, Dadin; Bunyamin, Bubun (Jurnal Istimā, 2024)
The Real Work Lecture Program (KKN) in Cipada Village is carried out to empower the community through various educational activities. This program includes teaching activities at PAUD Kuncup Harapan, SDN 1 Cipada, as well as the implementation of the Study Group and Tutoring program (KOBAR and BIMBEL). The main focus of the activity is to improve students' cognitive, social, and character abilities, as well as to instill awareness of the importance of higher education through educational seminars. The results of the program show success in creating a pleasant learning atmosphere and increasing student motivation. However, several challenges were encountered, such as limited educational facilities, short program duration, and logistical constraints. Community participation in some activities is also limited, which affects the sustainability of the program. Based on these findings, it is recommended to improve educational facilities, extend the duration of the program through the involvement of local tutors, and increase community participation in every stage of program planning and implementation. Adjustments to logistics and timing are also needed to maximize the impact.